The mythic meanings of the Second Amendment : taming political violence in a constitutional republic - Williams, David C., 1960- (Yale University Press, 2003)
David Williams offers a new reading of the Second Amendment suggesting that it guarantees to individuals a right to arms only insofar as they are part of a united & consensual people so that their uprising can be a unified revolution rather than a civil war.